다래끼 절개 배농술에서 병변내 스테로이드 주사 병행치료의 임상적 효과 - 이가혜; 장민욱 (검안 및 콘택트렌즈 학회지, 23(3), 2024)
목적: 다래끼 절개 배농술에서 병변내 스테로이드 주사 병행이 미치는 영향에 대해 알아보고자 하였다. 대상과 방법: 2015년 1월부터 2021년 1월까지 본원에서 다래끼 진단 하 절개 배농술을 받은 132명의 환자를 대상으로 절개 배농술 시행시 병변내 스테로이드 주사를 병행한 군과 병행하지 않은 군을 나눈 후 각 군에서 절개 부위에 따라 여러 항목들을 조사하였다. 결막 절개를 시행한 환자에서 수술 전후 붓기 정도, 재발률 및 재발하기까지의 기간을 비교하였고 피부 절개를 시행한 환자에서는 수술 전후 발적 정도, 재발률 및 재발하기까지의 기간을 비교하였다. 결과: 피부 절개로 절개 배농술을 시행한 군에서 수술 후 1주째 발적 감소 정도는 스테로이드 주사를 병행한 환자들에서 병행하지 않는 환자들에 비해 유의한 차이가 없었으며(p = 0.609) 결막하 절개로 절개 배농술을 시행한 군에서 수술 시행 1주째 붓기 감소 정도는 스테로이드 주사를 병행한 환자들과 병행하지 않는 환자들에서 차이는 없었다(p = 0.502). 절개 배농술만 시행한 환자에서 1개월 이후에도 다래끼가 남아있었던 비율은 0.04%, 절개 배농술과 스테로이드 주사를 병행한 환자에서는 0.02%로 두 군 간의 유의한 차이는 없었다(p = 0.414). 결론: 다래끼 치료에 있어 피부, 결막 절개로 절개 배농술을 시행할 때 병변내 스테로이드 주사 병행은 수술 후 발적, 붓기 호전에 영향이 없다. Purpose: To investigate the postoperative effect of intralesional steroid injection during incision and curettage of chalazia. Methods: From January 2015 to January 2021, patients who underwent incision and curettage for the diagnosis of chalazia were divided into groups: with or without intralesional steroid injection during incision and curettage. Incision and curettage were performed in 88 eyes, and concurrent intralesional steroid injection, incision, and curettage were performed in 44 eyes. Each group was further divided according to the incision site: subconjunctival or skin incisions. The degree of erythema, recurrence, and recurrence rate were reviewed in patients who underwent skin incisions, while the degree of swelling, recurrence, and recurrence rate, in those who underwent subconjunctival incisions. Results: In the group that underwent incision and drainage through skin incisions, no significant difference was observed in the degree of erythema reduction 1 week after surgery between patients treated with steroid injections and those without (p = 0.609). No difference was observed in the degree of swelling reduction 1 week after surgery between the two groups that underwent incision drainage with steroid injection and the group that did not (p = 0.502). No significant difference was observed between the two groups, with a rate of 0.04% of remaining chalazia after 1 month in patients who underwent incision and drainage alone and 0.02% in patients who received both incision drainage and steroid injections (p = 0.414). Conclusions: In the treatment of chalazia, concurrent intralesional steroid injections were not effective in the regression of postoperative lesional erythema and swelling. KCI Citation Count: 0